2008
DOI: 10.1002/rmv.589
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and treatment of adenovirus infections

Abstract: Adenoviruses (Ads) are common opportunistic pathogens that are rarely associated with severe clinical symptoms in healthy individuals. In contrast, in patients with compromised immunity, Ad infections often result in disseminated and potentially life-threatening disease. Among these are AIDS patients, individuals with hereditary immunodeficiencies and recipients of solid organ or haematopoietic stem cell transplants (HSCT) who receive immunosuppressive therapy. The latter account for the largest number of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
182
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(204 citation statements)
references
References 146 publications
7
182
2
3
Order By: Relevance
“…Although these diseases are self-limiting in immunocompetent individuals, they cause significant morbidity in AIDS, cancer, and organ transplant patients with compromised immune systems (2)(3)(4). Because of their broad cell tropism and ease of genome manipulation, replication-deficient or conditionally replicating HAdVs are also being evaluated in the clinic as potential vaccine and gene therapy vectors (5).…”
mentioning
confidence: 99%
“…Although these diseases are self-limiting in immunocompetent individuals, they cause significant morbidity in AIDS, cancer, and organ transplant patients with compromised immune systems (2)(3)(4). Because of their broad cell tropism and ease of genome manipulation, replication-deficient or conditionally replicating HAdVs are also being evaluated in the clinic as potential vaccine and gene therapy vectors (5).…”
mentioning
confidence: 99%
“…Sporadically, HAdVs can cause viral meningitis, encephalitis or hemorrhagic cystitis. 19 Because of its association with mild disease and a relatively easy to manipulate genome (as compared to other HAdV types/ species), most work on HAdV as vector for (cancer) gene therapy has been done with serotype 5 of species C. HAdVs have distinct advantages as a gene transfer vector, including high transfection efficiency of cells irrespective of their growth status. The genome of HAdVs is easy to manipulate for retargeting and insertion of transgenes, and efficient production of high titer virus stocks is possible.…”
Section: Family Herpesviridae: Herpes Simplex Virus 1 (Hsv)mentioning
confidence: 99%
“…It is important that early detection of Adenoviremia enables us to initiate therapy before a significant increase in mortality (La Rosa et al, 2001). Although less efficient than Cidofovir or Ribavirin, Ganciclovir can interfere with the function of adenovirus DNA polymerase, thus inhibiting viral replication in vitro (Lenaerts et al, 2008). In retrospective studies, lower incidences of adenovirus infections appeared to be reported in patients treated with Ganciclovir as cytomegalovirus prophylaxis (Bruno et al, 2003).…”
Section: Treatment To Avoid Hemodialysis Before and During Hemorrhagimentioning
confidence: 99%